Mapping the Research Landscape: A Bibliometric Analysis of Islam's Role in Sustainable Development - Sheikh Abu Toha Md Saky; Mohammad Zakki Azani; Muhammad Wildan Shohib; Md Nurul Islam (IKIP Mataram, 2024)
This bibliometric analysis delves into the expansive landscape of research where Islam intersects with sustainable development, covering the period from 1991 to 2023. The dataset, comprising 586 documents from 354 sources, signifies a dynamic and rapidly growing field, with an impressive annual growth rate of 11.44%. The relatively low average document age of 5.08 years highlights the contemporary nature of the research, while the high average citations per document (5.795) and substantial reference count (25,019) underscore the field's influence and interconnected character. Key contributors include Malaysia, with 369 articles, and Indonesia with 269 articles, emphasizing their leadership roles. The USA emerges as the most cited country, with 284 total citations, reflecting its significant impact. The global collaboration map highlights Malaysia as a central hub, collaborating notably with Indonesia, Bangladesh, and the USA, illustrating the collaborative nature of research in this area. Trending topics reveal a shift towards holistic themes like environmental protection, ethics, and public health. The enduring presence of keywords such as